IMPACT OF PATRONAGE MOTIVES ON CONSUMERS’ CHOICE OF RETAIL OUTLETS IN ENUGU METROPOLIS, ENUGU STATE, NIGERIA - Victor, Nnamani, Chukwuemeka; Ogba, Ike-Elechi Ph.D; Okafor, Okafor, Juliana Nkechi; Ogbuke, John Chukwudi (International Journal of Allied Research in Marketing and Management (IJARMM), 2024)
This Study Examined The Impact Of Patronage Motives On Consumers Choice Of Retail Outlets. Specific Objectives Are To; Examine Whether To What Extent Customer Service, Store Location, Store Atmosphere, Product Assortments, and Product Quality Individually Impact Consumers’ Of Retail Stores. The Major Entity Analyzed Is Actual Retail Outlets Consumers In Metropolis Enugu State, Nigeria. The Total Population Is 3, 267,837. Sample Size Of 356 Was Used In This Study. Multiple Regression Analysis With The Aid Of Spss Version 20 Was Used To Test The Hypotheses. Results Revealed That All The Five Predictors Of Patronage Motives Customer Service, Product Quality, Product Assortment, Store Location, And Store Atmosphere Significant. This Implies That, Customer Service, Product Quality, Product Assortment, Store Location, And Store Atmosphere Significantly Impact On Consumers’ Of Retail Outlets. The Study Concludes That Product Quality, Customer Service, Store Location, Store Atmosphere, Product Assortments, And Product Quality, Had A Significant Positive Impact On Customers’ Of Retail Outlets In Metropolis In Enugu State, Nigeria. The Study Therefore, Recommends That Retail Outlets Should Focus On Improving Quality Product For Their Consumers. They Should Try To Attract New Consumers And Retain Existing Ones Through Quality Products. Retail Outlets Should Concentrate On Offering Good Background Music, Lighting And Good Atmosphere For Customers. The Study Recommends That Product Assortments Should Be Improved Upon By The Retailers To Stimulate Consumer Patronage Motives. The Study Recommends That Retail Stores Should Be Located In Areas That Are More Convenient To Customers. This Study Has Provided Opportunities For Further Research Into The Impact Of Patronage Motives On Consumers’ Choice Of Retail Stores.